Warshah Amal fi Kitabah al-Maqalah al-Ilmiyyah wa Nasyriha fi al-Majallat al-Musannafah fi Qa'imah SCOPUS/ISI fi Majal al-Ulum al-Syar'iyyah wa al-Dirasat al-Islamiyyah - Sahrir, Muhammad Sabri (2021)
A 3-day international webinar on publishing in SCOPUS/WOS indexed journals with Umm al-Qura University, Saudi Arabia